The impact of Google Classroom to increase students’ information literacy - Citra Ayu Dewi; Muhali Muhali; Yeti Kurniasih; Diah Lukitasari; Abdul Sakban (Institute of Advanced Engineering and Science, 2022)
Information literacy at the higher education level is very important because it tends to be problematic in fostering students' critical thinking skills, including awareness, collection, understanding, analysis, synthesis, and the use of information and their attitudes to the treatment of information at the university level. This study examined the effects of the online learning Google Classroom in enhancing information literacy among students. This study observed a one-group pretest-posttest experimental design. This research involved 65 students from the Chemistry Course under the Biochemistry Program. The instrument used to assess students’ information literacy consist of fair set of multiple-choice questions. The test was found to be very valid at 4.22% and highly reliable at an alpha level of 0.86. The findings of this research showed that the information literacy of students improved before and after their learning exposure using Google Classroom based on the descriptive and inferential statistics. Moreover, the students' attitude towards the online platform shows that they are more willing to learn using Google Classroom than the non-online or conventional learning platforms. Therefore, applying Google Classroom in online learning is effectively boost students’ information literacy.